Analysis of Difficulties in Translating Arabic Texts for 9th Grade Students - Purnama, Boby Bagas; Setiyawan, Agung; Holilulloh, Andi; Sapar, Ahmad Arifin B. (Arabi : Journal of Arabic Studies, 2024)
The topic of this research aims to examine the difficulties that frequently occur when translating Arabic texts, the reasons behind these difficulties and the answers provided in the form of continuous assistance. The methods that were used in this research are both qualitative and quantitative. Data collection methods used in this study include documentation, interviews, and observation. Qualitative data was analyzed using reduction, data presentation and conclusion stages and quantitative data was analyzed using frequency distribution. The results of this research show that students' biggest difficulties in vocabulary are at 80%, Arabic grammar at 15%, and language interference at 5%. Linguistic and non-linguistic factors are the two categories of elements that affect translation errors. Solutions provided along with continuing assistance. The continuous assistance strategies that are provided include text selection, reference usage, language structure discussion, direct correction, context analysis of the text, sensitivity to cultural nuances and consistency in practice. It is envisaged that this will allow for the development of the supplied sustainable help.